Affecting Factors Performance of Lecturer Remains in the University of Muhammadiyah Buton - Rahim Rahim; Arfiah A (International Journal of Management Progress, 2020)
Lecturers are one of the essential components in an education system in higher education. The roles, tasks and responsibilities of lecturers are very meaningful in realizing the goals of national education, which are to educate the life of the nation, improve the quality of Indonesian people, cover faith and piety, noble character, and mastery of science, technology, and adaptation. Therefore it is necessary to pay great attention to matters relating to improving the performance of lecturers so that lecturers can carry out their tasks more professionally. This study aims to analyze the factors that influence the performance of Permanent Lecturers at Buton Muhammadiyah University. These factors are motivation, competency, leadership, and work environment. The subjects in this study were Permanent Lecturers at the University of Muhammadiyah Buton. The study was conducted using a questionnaire as an primary data collection instrument. Samples taken as many as 40 lecturers using the convinience samling method. To measure the factors that influence the performance of Permanent Lecturers at Buton Muhammadiyah University, multiple analysis is used. The results showed that the motivation, leadership competency, and the work environment of the lecturer had a positive influence on the performance of the Permanent Lecturer at Buton Muhammadiyah University.